Ливаний - Львовский в честь Преображения господня женский монастырь - Алексий (К 2000-летию Рождества Христова, 2016)
Экземпляры: (20181115) / Инвентарный номер: 1314 / Цена: / Сис.шифр: 86.372:3-0 / Авт.знак: П 68 / ББК: 86.372:3-0